The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1017/s1751731107001449
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ingesting a saltbush and barley ration on the carcass and eating quality of sheepmeat

Abstract: Forage halophytes such as saltbush (Atriplex spp.) are widely used to revegetate Australian saline land and can provide a medium-quality fodder source. An animal house experiment was conducted to investigate differences in the carcass and eating quality of sheep ingesting saltbush from saline land in combination with a barley supplement. Twenty-six merino hoggets (two groups of 13) were fed either a 60 : 40 dried saltbush (Atriplex nummularia): barley (S 1 B) ration or a 33 : 25 : 42 lupins : barley : oaten ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
3
13
0
3
Order By: Relevance
“…The sheep fed saltbush and barley supplement could then have a decreased energy availability, which in addition to the higher energy requirements to process salt (Arieli et al, 1989) would decrease the availability of energy for lipogensis. Sheep fed saltbush and barley supplement have also a higher proportion of lean meat compared to controls (Pearce et al, 2008). Lean muscle deposition is driven by a higher protein-to-energy ratio available in the diet (Searle et al, 1982;Campbell et al, 1984;Campbell, 1988), so, as described above, the increased rate of passage and protein available in response to salt intake could explain the associated increase in lean meat (Hemsley et al, 1975).…”
Section: Digby Chadwick and Blachementioning
confidence: 96%
See 2 more Smart Citations
“…The sheep fed saltbush and barley supplement could then have a decreased energy availability, which in addition to the higher energy requirements to process salt (Arieli et al, 1989) would decrease the availability of energy for lipogensis. Sheep fed saltbush and barley supplement have also a higher proportion of lean meat compared to controls (Pearce et al, 2008). Lean muscle deposition is driven by a higher protein-to-energy ratio available in the diet (Searle et al, 1982;Campbell et al, 1984;Campbell, 1988), so, as described above, the increased rate of passage and protein available in response to salt intake could explain the associated increase in lean meat (Hemsley et al, 1975).…”
Section: Digby Chadwick and Blachementioning
confidence: 96%
“…Lean muscle deposition is driven by a higher protein-to-energy ratio available in the diet (Searle et al, 1982;Campbell et al, 1984;Campbell, 1988), so, as described above, the increased rate of passage and protein available in response to salt intake could explain the associated increase in lean meat (Hemsley et al, 1975). It has to be noted that the pH or the color of meat or any eating quality attributes were not modified by feeding saltbush and barley supplement (Pearce et al, 2008). Figure 1 The renin-angiotensin system is responsible for the maintenance of salt and water balance.…”
Section: Digby Chadwick and Blachementioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, these dicots can be included as a significant component of a total mixed ration to provide energy and a nitrogen source for protein production. It has recently been shown that halophytes can be included as a significant component of a feedlot diet in a series of experiments investigating how consumption of halophytes influences meat eating quality [49,50,62,63]. Sheep that were fed diets that contained a high proportion of halophytes exhibited moderate weight gain and produced meat with a high eating quality (determined by a taste panel) and the meat also had extended shelf life.…”
Section: Use Of Saline Water For Terrestrial Agriculturementioning
confidence: 99%
“…According to Pearce, Pethick and Masters (2008), increased propionate production stimulates insulin concentration, which is the hormone regulating the fat deposition in the carcass. However, in the present study, the SFC only increased fat thickness, with no effects on ADG or G:F ratio.…”
Section: Intake Performance and Carcass Traitsmentioning
confidence: 99%